Overview of the Incidence of Scabies Factors in the Work Area of the Public Health Center Tanjung Medan, Kampung Rakyat District - Mutiara Nauli Siregar; Rika Arnanda; Sarah Fadhila Siregar; Apriliani Apriliani; Wasiyem Wasiyem; Nurhayati Nurhayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Based on health profile data in the work area of the Tanjung Medan Community Health Center, Kampung Rakyat District, South Labuhanbatu (June 2019-June 2020), the number of cases of scabies sufferers was 352 cases. The areas where people living with scabies disease are prone to frequent flooding when it rains, because people live along rivers and are also densely populated, so this has resulted in a high number of cases of scabies.This study was conducted to determine the description of the incidence of scabies in the working area of PUSKESMAS Tanjung Medan, Kecamatan Kampung Rakyat.This study uses qualitative methods. The research informants were selected by using purposive sampling method. The criteria for the informants in this study were people who had or are currently suffering from scabies skin disease. Data were collected by in-depth interviews.The results showed the factors that influence the incidence of scabies such as personal hygiene, environmental sanitation, nutritional status, symptoms of scabies experienced, and health services at PUSKESMAS. In the aspect of personal hygiene, it is known how the informants' daily activities in carrying out personal hygiene. The personal hygiene of the community and, the environmental sanitation around the place where the community lives is still not good. It is also known that a poor diet has made supporting factors for the development of scabies continue to occur, in the community, so that people continue to experience symptoms such as itching and the appearance of red spots on the skin.